Antisymmetric linear magnetoresistance and the planar Hall effect - Yishu Wang (Nature Portfolio, 2020)
Magnetoresitance (MR) is a tool to study electronic transport and spin order in metals. Here, the authors demonstrate two different microscopic origins of antisymmetric linear MR from both Zeeman-split Fermi surface and anomalous electron velocity.